Development of personality in a family - Bilyk О. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
One of terms of families happiness – aspiring to development. Problems arise up then, when people stop to put be for itself aims and stop to develop. Aspiration and possibilities of development depend on the stage of family. By reason of conflicts and can be when one or both partners cannot capture skills, necessary for passing to other stage of relations.